Recurrence free decomposition formulas for the Lauricella special functions - Ergashev, T.G.; Ryskan, A.R.; Yuldashev, N.N. (Karagandy University of the name of acad. E.A. Buketov, 2024)
Expansion formulas associated with the multidimensional Lauricella hypergeometric functions are wellestablished and extensively utilized. However, the recurrence relations inherit in these formulas add extra complexities to their use. A thorough analysis of the characteristics of these expansion formulas shows that they can be simplified and converted into a more convenient form. This paper presents new recurrence free decomposition formulas, which are employed to solve boundary value problems.
Expansion formulas associated with the multidimensional Lauricella hypergeometric functions are wellestablished and extensively utilized. However, the recurrence relations inherit in these formulas add extra complexities to their use. A thorough analysis of the characteristics of these expansion formulas shows that they can be simplified and converted into a more convenient form. This paper presents new recurrence free decomposition formulas, which are employed to solve boundary value problems.
Keywords: Appell Functions; Lauricella Functions; Recurrence Decomposition Formula; Recurrence Free Decomposition Formula